Low-DMGD, Large-Effective-Area and Low-Bending-Loss 12-LP-Mode Fiber for Mode-Division-Multiplexing - Huan Zhang; Jian Zhao; Zhiqun Yang; Guanju Peng; Zixiang Di (IEEE Photonics Journal)
We report the design of 12-LP-mode (21-spatial-mode) fiber with a low differential mode group delay (DMGD), a large effective area, and a low bending loss that is adapted to a mode-division-multiplexing system over the C+L band. Based on the designed fiber parameters, we characterize the few-mode fiber (FMF) with the DMGD, an effective area, and a bending loss. Over the C+L band, the maximum DMGD is 0.106 ps/m, and the effective area is in the range of 150∼485 μm2. The bending loss of the designed FMF reduces to zero when the bending radius is greater than 9 mm, and the DMGD is below 0.0413 ps/m at the wavelength of 1550 nm.